Business Development Strategy Using the Business Model Canvas (BMC) Approach in Increasing Sales Volume at MSME Mojokerto Sayur (MOSAY) - Naura Husnina Athifanita Putri; Siti Ning Farida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Businesses today are increasingly developing following the needs of the market, such as the existence of a packaged vegetable business that was created because of this. Mojokerto Sayur (MOSAY) is one of the many packaged vegetable businesses in Mojokerto that faces challenging conditions and dynamic competition. This condition also makes MOSAY's sales turnover experience a decline to an increase that has not been able to reach the target every month. Therefore, MOSAY needs an appropriate business model and requires the implementation of new strategies in order to increase its sales volume. This research aims to analyze MOSAY's business model with the Business Model Canvas (BMC) approach which will then be evaluated according to SWOT analysis so that it will create recommendations for improvement in each element of the business model. This research uses a qualitative descriptive method with data analysis techniques using BMC and SWOT analysis which includes the use of IFAS and EFAS. Data collection techniques were carried out by observation, in-depth interviews and documentation studies. Informants in this study were selected purposively totaling 10 people consisting of owners, employees and consumers of MOSAY. The results showed a strategy that leads to supporting an aggressive strategy or “Growth Oriented Strategy” on the SWOT analysis diagram which will be used as a recommendation for BMC improvement. The implementation results show that each element in BMC requires improvement recommendations with the resulting strategy can be used as a consideration by MOSAY in making business decisions.